Assessing the clinical reliability of short-term heart rate variability: insights from controlled dual-environment and dual-position measurements - C. Besson; A. L. Baggish; P. Monteventi; L. Schmitt; F. Stucky; V. Gremeaux (Scientific Reports)
Abstract Heart rate variability (HRV) is a widely recognized biomarker for autonomic nervous system regulation, applicable in clinical and athletic settings to monitor health and recovery. Despite its extensive use, HRV measurement reliability is influenced by numerous factors, necessitating controlled conditions for accurate assessments. This study investigates the reliability of short-term HRV measurements in various settings and positions, aiming to establish consistent protocols for HRV monitoring and interpretation. We assessed morning HRV in 34 healthy, physically active adults across supine and standing positions, at home and in the laboratory, over a 24-hour period. Environment significantly impacted standing HRV. Home measurements exhibited slightly lower variance compared to lab settings, underscoring the importance of environment control. Our findings confirm the high reliability of HRV measurements, indicating their robustness in capturing autonomic changes, provided a rigorous methodology is employed. Here we show that effective and reliable HRV assessment is possible across various conditions, contingent upon strict management of confounding factors. This research supports the utility of HRV as a non-invasive diagnostic tool, emphasizing its importance in health management and potential in broadening applications to diverse populations. Future studies are encouraged to expand these assessments to include varied demographic and clinical profiles, enhancing HRV integration into routine health evaluations.